2017
DOI: 10.1159/000456534
|View full text |Cite
|
Sign up to set email alerts
|

Post-Progression Survival Associated with Overall Survival in Patients with Advanced Non-Small-Cell Lung Cancer Receiving Docetaxel Monotherapy as Second-Line Chemotherapy

Abstract: Background: In patients with non-small-cell lung cancer (NSCLC), the effects of second-line chemotherapy on overall survival (OS) might be confounded by subsequent therapies. Therefore, using individual-level data, we aimed to determine the relationships between progression-free survival (PFS) and post-progression survival (PPS) with OS in patients with advanced NSCLC treated with docetaxel monotherapy as second-line chemotherapy. Methods: Between April 2002 and December 2014, data from 86 patients with advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 38 publications
0
17
2
Order By: Relevance
“…In contrast with the findings of previous studies, some reports of individual levels did not find PFS to be a surrogate endpoint for OS in advanced lung cancer patients, although PPS was not evaluated in those studies. These reports found that PFS was much shorter than PPS.…”
Section: Clinical Significance Of Post‐progression Survival (Pps)contrasting
confidence: 86%
See 4 more Smart Citations
“…In contrast with the findings of previous studies, some reports of individual levels did not find PFS to be a surrogate endpoint for OS in advanced lung cancer patients, although PPS was not evaluated in those studies. These reports found that PFS was much shorter than PPS.…”
Section: Clinical Significance Of Post‐progression Survival (Pps)contrasting
confidence: 86%
“…These reports found that PFS was much shorter than PPS. Thus, PPS was closely related to OS – in fact, the relationship was linear . The fact that PPS accounted for the majority of OS suggests that the chemotherapy used was not sufficiently effective for PFS to be a significant component of OS.…”
Section: Clinical Significance Of Post‐progression Survival (Pps)mentioning
confidence: 98%
See 3 more Smart Citations